Clinical case of ventricular septal rupture in patient with acute myocardial infarction - V. D. Syvolap; O. V. Nazarenko; Ya. V. Zemlyaniy (Zaporožskij Medicinskij Žurnal)
This article describes ventricular septal rupture in the acute phase of myocardial infarction after thrombolytic therapy. The peculiarity of this case is the lack of patient expressed pain and minimal manifestations of heart failure on the background specific to ventricular septal rupture ECG changes and echocardiographic data. To analyze the main factors giving the opportunity to assess the risk of this complication in patients with acute myocardial infarction. The clinical case demonstrates the success of the conservative management of patient with acute myocardial infarction complicated by early ventricular septal rupture.